KEPADATAN LARVA NYAMUK AEDES sp DENGAN KEJADIAN PENYAKIT DEMAM BERDARAH DANGUE (DBD) - Jernita Sinaga; Helfi Nolia; Desy Ari Apsari; Widia Ayu Sagala (Poltekkes Kemenkes Medan, 2022)
Dengue hemorrhagic fever (DHF) is an acute febrile viral disease that is often accompanied by symptoms such as headache, bone or joint and muscle pain, rash, and low or low white blood cell count, transmitted by mosquitoes through the bite of the Aedes mosquito. The purpose of this study was to determine whether there was correlation between the density of Aedes sp mosquito larvae and the incidence of Dengue Hemorrhagic Fever (DHF) in the working area of ??Tanah Jawacommunity health Center, Tanah Jawasub district, Simalungundistrict in 2022. This type of research was an analytic survey with a cross sectional design. The population in this study were all houses in Tanah Jawa and the sample was determined by random sampling technique with the provisions of ABJ as many as 100 houses. Collecting data in this study using questionnaires and observation sheets, the data analysis used was univariate and bivariate analysis using chi-square test. The results of this study indicated that the daily water reservoir p value was 0.009 p (0.05), mosquito larvae density p value was 0.008 p (0.05) meaning that there was a significant correlation between daily water reservoirs, the presence of mosquito larvae with the incidence of Dengue Hemorrhagic Fever (DHF), Not a water reservoir p value of 0.786 p (0.05) means that there was no significant correlation between non-water reservoirs and the incidence of DHF, and the value of the larval density index House Index (HI). ) (31%), Container Index (CI) (5%), Breathe Index (BI) (33%) was categorized as medium density, and the value of Larva Free Rate (ABJ) (69%) was categorized as high. The conclusion in this study was that there were Aedes sp mosquito larvae and there was correlation between the density of Aedes sp mosquito larvae with the incidence of dengue fever and dengue fever in the working area of ??the Tanah JawaCommunityHealth Center, Tanah Jawa District, Simalungun district in 2022.